The Role of Strategic Management and Modern Agricultural Technology in Developing Field Crops Cultivation - Raad Fahad Almasshadni; Redvan Ghasemlounia (International Journal of Engineering and Management Research, 2021)
The research aims to determine the role of agricultural system managers in Iraq in the field of strategic management and agricultural technology in developing field crops cultivation, and to achieve the objectives of the research, the researcher prepared A five-Axis questionnaire, which included 40 paragraphs for middle and executive directors, divided into five Axis, and dealt with [content, a questionnaire that included message scale, strategic analysis, vision formulation, characteristics of importance, objectives, types of strategies, strategy levels, strategy characteristics, strategy implementation, strategy evaluation. The research was carried out as a random sampling from agricultural departments from the governorate of Baghdad. After the questionnaire was done in the Google Documents program, the questionnaire was published on the social media sites of those involved in the agricultural sector and sent by e-mail to some managers and their assistants as it was not possible to provide them with the questionnaire on paper due to the Corona pandemic. A random sample was withdrawn by 55% of each category of the research community. Thus, the total sample size is 100. The weighted average, F-test, and LSD were used to analyze the data and obtain results using the SPSS program. One of the results of the research was that the general character of the level of experience in strategic management of agricultural system managers at the administrative levels [middle, executive] in the field of strategic management, general, was medium, The managers of the agricultural system need to be developed, and this is reflected in their knowledge capabilities in the field of strategic management to improve the level of performance of the units responsible for them. The researcher recommends the need to qualify the managers of the upper and middle departments and send them outside the country to acquire new concepts in strategic management and the need to increase their knowledge and skill capabilities in developing the strategy at the middle and executive levels] through specialized training programs in the field mentioned above.